Analisis Pengendalian Kualitas Produk Pakan Ternak pada PT XYZ dengan Metode Six Sigma dan FMEA - Armevia, Nazwa Rifqi; Nugraha, Isna (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Product quality has an important role in maintaining customer trust and the sustainability of the company. PT XYZ, which produces various types of animal feed, faces the problem of defects in pellet products, such as different feed size shapes, hot feed temperatures, and uneven feed colors. These defects not only affect production efficiency but can also reduce customer satisfaction. This research needs to be carried out so that PT XYZ can identify the cause of the defect and provide improvement proposals using the Six Sigma method through the DMAIC (Define, Measure, Analyze, Improve, Control) stage with Failure Mode and Effect Analysis (FMEA). The results showed that the main causes of defects were unstable engine condition, suboptimal cooling system, and dirty or worn engines, with the highest RPN values of 504, 210, and 448, respectively. The proposed improvements include standardization of engine settings, routine maintenance, and machine cleaning before use. The implementation of this recommendation is expected to improve product quality, reduce defects, increase operational efficiency, and strengthen the company's competitiveness. In addition, this research also provides continuous guidance for PT XYZ in managing a more standardized and quality production process to achieve a competitive advantage in the market. Keywords: DMAIC, FMEA, Product Quality, Six Sigma